International Shipping The Role of Sea Transport in the Global Economy - Witthohn, Ralf (Springer, 2023)
Based on thoroughly researched texts and rare photographies this book describes the actual developments of international shipping and all the facets connected to overseas good flows. Main source for the deep reaching insight into the maritime industry are authentic reports carried out at the focusses of the shipping scene. By explaining the design und purpose of nowadays ship types, the different ways of cargo handling as well as the activities of shipowners and operators is painted a representative and rich-illustrated picture of the actual maritime scene.